Shallow groundwater near a deep-well CO2 storage site—15 years of stable water quality for agricultural use - Zhou, Zibo; Zhang, Kexin; Callahan, Damien L.; Timms, Wendy (Environmental science and pollution research international, 2025)
Injecting CO 2 into deep geological formations can be an effective carbon removal and storage technology to mitigate global climate change. Interaction of injected CO 2 with rock formations changes pH and hydrochemistry within the deep injection zone (> 800 m depth). However, cap rocks and multiple tight aquitards typically act as barriers to protect the shallow aquifer from changes in the injection zone. Monitoring and evaluation of shallow groundwater quality are essential to verify that carbon capture storage projects (CCS) do not impact the near-surface environment. This study investigated shallow groundwater quality using long-term data (2006–2023) from a regular monitoring program at the Otway International Test Centre (OITC) in Victoria, Australia. It was found that shallow groundwater quality was stable over at least 15 years, during which time three phases of CO 2 injection into a deep storage zone occurred. The results highlighted groundwater quality complied with guidelines of Food and Agriculture Organization (FAO) and Australian water quality guidelines. Minor and localised changes observed in salinity or pH in shallow monitoring piezometers were caused by natural processes. Moreover, a wide range of groundwater quality indicators were evaluated. The results demonstrated that the groundwater quality of shallow aquifers (< 80 m) at OITC is suitable for agriculture. The study provides assurance and confidence to stakeholders that the quality of the near-surface environment has not been impacted by CO 2 injection into confined formations and no pollution has been detected. Although numerous CCS sites around the world are subject to monitoring, no evidence of changes in shallow groundwater quality has been reported that could be traced to CO 2 injection in confined formations at > 800 m depth.